OPTIMALISASI KOMPETENSI MUJTAHID DALAM KERANGKA KAJIAN HUKUM ISLAM - Sindia Ayu; Meirison; Salma (JAS : Jurnal Ahwal Syakhshiyyah, 2024)
Abstract A mujtahid is called a Muslim scholar or cleric who has the qualifications and expertise to carry out ijtihat, namely the process of interpreting Islamic law based on its sources. This research uses a qualitative descriptive research method with a focus on studying concepts and content through library research. This research aims to analyze mujtahid competence, classical and contemporary mujtahid requirements, and mujtahid rankings. This study examines the competence of a mujtahid in the context of understanding and applying sharia law in Islam. Mujtahid competency was found to require a deep understanding of various sources of Islamic law, such as the Al-Qur'an, hadith, ijma', qiyas, asbab al-nuzul, and maqashid sharia. In addition, the ability to recognize and differentiate between the tasyri'iyah sunnah and the tasyri'iyah ghairu sunnah and to avoid violations of ijma' is also needed. Islamic ethics and values are also an integral part of a mujtahid's competence, assisting in making appropriate legal decisions. This study emphasizes that the competence of a mujtahid is an important element in maintaining integrity and accuracy in the ijtihad process, which is important in carrying out his duties as a guardian of sharia law. The findings in this research are that a mujtahid must have in-depth knowledge, analytical skills, and high moral integrity to carry out his duties in understanding and applying sharia law correctly.   Keywords: Mujtahid, Ijtihad, contemporary, classic